The Possibility for Improving Damage Tolerance of Integral Airframe Structure by High Strength Bonded Straps - Jetela, Vaclav; Klement, Josef; Augustin, Petr (Manufacturing Technology Journal, 2018)
Integral stringer panels can attain weight reduction in primary aircraft structures, but do not contain the physical barriers for a fatigue crack growth. One of the promising techniques for prolonging a fatigue crack growth is bonded crack retarders made of materials with high stiffness. An experimental study was done on two specimens with different geometries. High strength bonded straps made of corrosion resistant steel AISI 301 were adhesively bonded to Center-Cracked Tension (CCT) specimens made of aluminium alloy 2024-T351 and fabricated by a high-speed machining process to promote fatigue crack growth retardation. Specimens were tested at a constant amplitude load. The study concludes that the fatigue crack growth life can be significantly improved. Experimental results were compared with a prediction based on the VCCT technique and the NASGRO equation.
Keywords: Bonded crack retarder; Damage tolerance; Fatigue crack growth; Integral structure; Strap